Hydrophilic chelators for coordination and separation of radioactive f-block elements - Li Bin; Bao Mingjie; Kang Yu; Wang Ludi; Liu Yaoyang; Wang Li; Xu Chao (National Science Open)
Hydrophilic chelators are crucial for coordinating and separating radioactive f-block elements in nuclear fuel recycling, hazardous waste treatment, environmental remediation, radiopharmaceuticals, and related fields. However, their development and understanding lag behind their lipophilic counterparts. This review summarizes the development of hydrophilic ligands across four categories based on their structural similarities and chronological order. For each category, representative examples are discussed, highlighting their advantages and disadvantages. The review also benchmarks ligands from different groups, outlines current design challenges, and emphasizes the importance of establishing structure-function relationships to guide future ligand design. Additionally, we propose four novel f-block chelating ligands, some of which have shown efficiency in solid-liquid or membrane-based radionuclide separation, aiming to inspire the search for more robust systems for f-block element utilization and recycling. This review aims to provide a comprehensive overview of hydrophilic f-block element chelators and suggest promising approaches for future ligand development.